Upaya Pemberantasan dalam Penyelesaian Tindak Pidana Narkotika di Wilayah Hukum Kepolisian Resor Kota Denpasar - Kaley, Marthen Loghe; Aryana, I Wayan Putu Sucana (Jurnal Studi Pemerintahan dan Akuntabilitas, 2023)
Purpose: The problem of Narcotics today is enough to seize public attention. The target of victims is not only adults, children are also many victims of narcotics distribution. Narcotics is also used as a promising business event and continues to grow rapidly, this activity is certainly a negative impact such as mental damage both physically and psychologically narcotics users, especially the younger generation. In fact, the younger generation is the generation that is expected to become a successor to the Indonesian nation going forward. From the fact that there are, even though there have been severe criminal sanctions, but the perpetrators of narcotics crimes still exist until now so it is necessary to eradicate efforts in solving narcotics crime. Based on the background described, as for the formulation of the problem in writing this thesis, What are the obstacles in eradicating the completion of narcotics crime in the jurisdiction of the Denpasar City Police and how the eradication efforts in the resolution of narcotics crime in the jurisdiction of the Denpasar City Police. Method: To answer the formulation of the problem using the normative juridical approach, using the statutory approach, the concept approach. Sources of legal materials used are primary, secondary sources. The theory used emphasizes the theory of legal certainty so as to achieve the completion of narcotics crime in the area of ??Denpasar City Police Department Law. Result: The process of this research has found that eradication efforts in the resolution of narcotics crimes in the Denpasar City Police Legal Area have constraints in facilities, infrastructure and lack of public awareness. Efforts made in the eradication of narcotics crime in the Denpasar City Police Legal Area through Preventive (preventive) and Repressive (enforcement) efforts.